2000
DOI: 10.1002/(sici)1521-186x(200004)21:3<151::aid-bem1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Low-level exposure to pulsed 900 MHz microwave radiation does not cause deficits in the performance of a spatial learning task in mice

Abstract: There is some concern that short‐term memory loss or other cognitive effects may be associated with the use of mobile cellular telephones. In this experiment, the effect of repeated, acute exposure to a low intensity 900 MHz radiofrequency (RF) field pulsed at 217 Hz was explored using an appetitively‐motivated spatial learning and working memory task. Adult male C57BL/6J mice were exposed under far field conditions in a GTEM cell for 45 min each day for 10 days at an average whole‐body specific energy absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 40 publications
3
45
1
Order By: Relevance
“…There was no difference between rats exposed for 45 min to 3.5 W/kg and sham exposed or cage control rats in performance of these tasks. A similar study using mice [Sienkiewicz et al, 2000] studied the effect of exposure to low intensity 900 MHz RFR pulsed at 217 Hz with a spatial learning and working memory task. Mice were exposed under far field conditions in a GTEM cell for 45 min each day for 10 days at an average whole body specific energy absorption rate (SAR) of 0.05 W/kg.…”
Section: Microwave Effects On Cognitive Behavior Effects On Cognitivementioning
confidence: 99%
“…There was no difference between rats exposed for 45 min to 3.5 W/kg and sham exposed or cage control rats in performance of these tasks. A similar study using mice [Sienkiewicz et al, 2000] studied the effect of exposure to low intensity 900 MHz RFR pulsed at 217 Hz with a spatial learning and working memory task. Mice were exposed under far field conditions in a GTEM cell for 45 min each day for 10 days at an average whole body specific energy absorption rate (SAR) of 0.05 W/kg.…”
Section: Microwave Effects On Cognitive Behavior Effects On Cognitivementioning
confidence: 99%
“…In contrast, no effect of RF‐EMF exposure on spatial learning and working memory tasks was found [Sienkiewicz et al, 2000; Dubreuil et al, 2003; Maaroufi et al, 2014]. Moreover, other studies have reported a beneficial effect of RF‐EMF on cognitive function [Dragicevic et al, 2011; Arendash et al, 2012; Banaceur et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Cosquer also studied the effect of exposure to a 2 450 MHz electromagnetic field on the behavior of the rats after 45 minutes of irradiation in an elevated maze and found that electromagnetic radiation had no effect on the rats' behavior (2). Furthermore, irradiation with waves at a frequency band of 900 MHz in radial and water mazes had no effects on the rats' spatial memory function (3,4,19,20). In one study, Dubreuil et al (3) showed that exposure to GSM-900 electromagnetic fields for 45 minutes before each training (10 days) had no effects on spatial learning in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Jadidi, 45 minutes of exposure to mobile phone radiation at 950 MHz had no effects on learning and the memory acquisition phase in rats (19). Sienkiewicz studied the effect of an electromagnetic field at 900 MHz on spatial learning in rats using an eight-armed radial maze and found that placing the rats in this field for 45 minutes each day for 10 consecutive days had no effects on their memories (20). However, at these frequency bands, cell phone waves affect human memory (21,22) and some of the studies have used water and radial mazes at a frequency of 2 450 MHz (7,8,23).…”
Section: Discussionmentioning
confidence: 99%